2018
DOI: 10.1002/ijfe.1675
|View full text |Cite
|
Sign up to set email alerts
|

Topological applications of multilayer perceptrons and support vector machines in financial decision support systems

Abstract: The heart of this study is particularly on risk assessment of financial decision support systems (FDSSs), to advance the model performance and improve classification accuracy. To conquer the downsides of the classical models, statistical intelligence (SI) technologies, for example, multilayer perceptrons (MLPs) and support vector machines (SVMs), have been deliberated in FDSS applications. Recently, the prestigiousness of SI approaches has been confronted by the latest prediction learners. Therefore, to ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 104 publications
(209 reference statements)
0
13
0
Order By: Relevance
“…The amount of data for the pre-COVID-19 time period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) was 5216 daily observations for all the used currencies, and for the COVID-19 period 571 observations. The training set of the pre-COVID-19 dataset was cross validated tenfold to minimise the training error and enhance the generalizability of the forecasting outcome (Abedin et al, 2019).…”
Section: Experimental Datamentioning
confidence: 99%
“…The amount of data for the pre-COVID-19 time period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) was 5216 daily observations for all the used currencies, and for the COVID-19 period 571 observations. The training set of the pre-COVID-19 dataset was cross validated tenfold to minimise the training error and enhance the generalizability of the forecasting outcome (Abedin et al, 2019).…”
Section: Experimental Datamentioning
confidence: 99%
“…Furthermore, our model is perfect when dealing with small datasets. The use of RotF was found to be robust and stable than extreme ML, SVM, and neural networks, especially with small training sets (Abedin et al, 2019 ; Han et al, 2018 ). Thus, our model would be of great usefulness for SMEs that particularly deal with small datasets.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Abedin et al assessed the risk of financial decision support systems (FDSSs) and applied MLPs and SVMs in credit scoring and bankruptcy prediction. They confirmed that MLP5‐5 and MLP4‐4 are practicable topologies for the MLP algorithm, and the linear kernel function-trained SVM has better performance in prediction 47 .…”
Section: Related Literaturementioning
confidence: 63%